Review Article on Effectiveness of Isometric Exercise on Osteoarthritis - R. , Ramani; V. , Hemavathy (International Journal of Psychosocial Rehabilitation, 2020)
The isometric exercises for the osteoarthritis of the knee have been designed to strengthen the thigh muscles without much movement around the knee joint. The strength of the quadriceps muscles affects the knee joint functions. It is evident that lower extremity strength has a major role in knee joint shock attenuation during weight-bearing activities. There is an increased risk of development or progression of osteoarthritis due to greater or uncontrolled loading on the knee joint. Reduction of pain and disability is the main aim of the treatment approach in the management of knee osteoarthritis. Isometrics are a type of strength training in which the joint angle and muscle length do not change during contraction (compared to concentric or eccentric contractions, called dynamic/isotonic movements).